Soda Taxes, BMI and Obesity: Evidence from Seattle - James Flynn; Anja Gruber (Institute of Labor Economics (IZA), 2025)
This paper uses restricted-access data from the Behavioral Risk Factor Surveillance System Survey to assess whether the sugar-sweetened beverage (SSB) tax levied in Seattle in 2018 led to declines in body mass index (BMI) and the rate of obesity. We implement an event-study design which compares these outcomes in the treated region to those of untaxed areas. We find no evidence of divergence in trends prior to the tax, followed by large declines in both outcomes after the tax was implemented. We estimate that the tax led to a reduction of .61 BMI points and reduced the obesity rate by 4.5 percentage points. Declines were largest for individuals with lower incomes, those without a college degree, and younger people, which are all groups who tend to consume more SSBs at baseline. We address concerns that our results are driven by the COVID-19 pandemic and provide suggestive evidence that SSB taxes improved these outcomes in other SSB-taxed jurisdictions as well. Our study adds to the growing evidence that SSB taxes can improve public health, rather than only affecting prices, purchasing, or consumption of taxed beverages.
Keywords: H2; H3; I12; I18; 330; soda tax; health behavior; taxation; obesity